Application of Inquiry-Based Learning Model to Improve Student Learning Outcomes on Redox Reaction Material for Class X Students at MAS Al-Khoir - Nasution, Annisa; Siregar, Nur Fauziah; Hasibuan, Nur Azizah Putri (LAVOISIER: Chemistry Education Journal, 2024)
This study aims to see the results of the application of the Inquiry-Based Learning Model in improving student learning outcomes in Redox Reaction subject matter for Class X Mas Al-Khoir Mananti Sosa Jae Village, Kec. Huta Raja Tinggi, Kab. Padang Lawas. The type of research used in this research is Classroom Action Research. Mas Al-Khoir Mananti Sosa Jae Village, Kec is the location used in this research. Huta Raja Tinggi, Kab. Padang Lawas. Data collection instruments are through tests and observations. The analysis method used in this research is quantitative analysis. Based on the results of the study show that there is an increase in student learning outcomes with the application of an inquiry-based learning model of redox reaction material for students of grade X from pre-cycle, cycle I to cycle II. Where the percentage of students who completed was 25% in pre-cycle, then increased in cycle I session 1 to 33.4%, then increased in cycle I session 2 to 60%, then increased in cycle II to 86.7%. The percentage of students who did not complete decreased from 75% in the pre-cycle, decreased to 66.6% in Cycle I Session 1, decreased to 40% in Cycle I Session 2, and decreased to 13.3% in Cycle II. The average score of the students increased from 54.3 before the cycle, then increased from 59.3 in cycle I to 68, then increased to 80 in cycle II. Following the indicators of success of this action, where students have passed the KKM (≥7).